Analisa Kelongsorang Lereng Akibat Dari Peningkatan Kadar Air YangTinggi - Rinaldi, Muhamad Rizki; Afriani, Lusmeilia; Hadi, Yohanes Martono (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
The level of slope safety is influenced by several factors. Such as slope conditions with largeloads, steep slopes and heavy rain conditions. This often results in landslides around the TransSumatra toll road, Pematang Panggang. So that around the slopes reinforcement is needed so thatthe slopes are more stable.Based on the results of laboratory tests and research in the field, the results of the calculation ofthe slope safety value program with a 30% saturation degree condition, the safe factor value is1.2946, the degree of saturation 40%, the safe factor value is 1.2881 and the degree of saturationis 60%, the safety factor value is equal to 1,2761. Because the lowest safe factor value is at 60%saturation degree, slope stability is handled at 60% saturation degree, which is strengthened bythe cutting method on the slope body and using sheet pile to get slope reinforcement. Two methodsof handling slope stability were carried out. From the comparison of slope stability handling with60% degree of saturation, the safe slope conditions are in handling one because there is nosubsidence and soil displacement to the free slope area.